MICA sounding rocket observations of conductivity‐gradient‐generated auroral ionospheric responses: Small‐scale structure with large‐scale drivers. Issue 11 (3rd November 2015) - Lynch, K. A.; Hampton, D. L.; Zettergren, M.; Bekkeng, T. A.; Conde, M.; Fernandes, P. A.; Horak, P.; Lessard, M.; Miceli, R.; Michell, R.; Moen, J.; Nicolls, M.; et al.
Abstract: A detailed, in situ study of field‐aligned current (FAC) structure in a transient, substorm expansion phase auroral arc is conducted using electric field, magnetometer, and electron density measurements from the Magnetosphere‐Ionosphere Coupling in the Alfvén Resonator (MICA) sounding rocket, launched from Poker Flat, AK. These data are supplemented with larger‐scale, contextual measurements from a heterogeneous collection of ground‐based instruments including the Poker Flat incoherent scatter radar and nearby scanning doppler imagers and filtered all‐sky cameras. An electrostatic ionospheric modeling case study of this event is also constructed by using available data (neutral winds, electron precipitation, and electric fields) to constrain model initial and boundary conditions. MICA magnetometer data are converted into FAC measurements using a sheet current approximation and show an up‐down current pair, with small‐scale current density and Poynting flux structures in the downward current channel. Model results are able to roughly recreate only the large‐scale features of the field‐aligned currents, suggesting that observed small‐scale structures may be due to ionospheric feedback processes not encapsulated by the electrostatic model. The model is also used to assess the contributions of various processes to total FAC and suggests that both conductance gradients and neutral dynamos may contribute significantly to FACs in a narrow region where the current transitions from upward to downward. Comparison of Poker Flat Incoherent Scatter Radar versus in situ electric field estimates illustrates the high sensitivity of FAC estimates to measurement resolution. Key Points: Auroral sounding rocket observations are reported We combine ground‐based, in situ, and modeling results We report gradient scale lengths in auroral structures